Aplikasi Peminjaman Ruangan Rapat Kantor Gubernur Provinsi Kepulauan Bangka Belitung Berbasis Android - Rendy Rian Chrisna Putra; Eza Budi Perkasa (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2019)
The loan of meeting room in the office of Bangka Belitung Province governor is currently still through the manual process that is lending must meet the manager who is in the office of the governor to obtain approval on lending The required room. Lending room that is still manual will be changed to Android based. The built-in system that will be built using the Java programming language with the helper platform is Android Studio, PHP, and MySQL database. The system's analytical techniques used in this research are object-oriented and use a Unified Modelling Language (UML) modeling tool to illustrate built-in applications. This research result shows that this room loan application can be used by the user well and can borrow room with this application. With this application is expected to help users to more easily borrow the room.